Spokane County cemetery guide photographs. - Roberts, Ann J.
Color photographs of Spokane County Cemeteries taken by Ann J. Roberts for her book, Spokane County Cemetery Guide. Reproductions of some of these photographs were included in the 2006 update of the Cemetery Guide. Photographs include individual graves as well as entire cemeteries. The photographs are labeled with their locations and the page in the book.